Personal Finance Knowlegde and Practice: An Opinion Survey with Employed and Self-employed People in Pokhara - Sharma, Puspa Raj; Bohara, Yub Raj (Journal of Nepalese Business Studies, 2012)
The ability to manage personal finances has become increasingly important in today's world. People must plan for long - term investments for their retirement and children's education. They must also decide on short - term savings and borrowing for daily life like a down payment for a house, a car loan, and other big - ticket items. Additionally, they must manage their different risk and insurance needs. This is might be the first survey about 'Personal Financial Knowledge and Practice' survey was conducted in 2011 with employed and Self-Employed people in Pokhara, Nepal. The survey revealed encouraging findings about how Employed and Self-Employed people of Pokhara approach money matters. This Personal financial literacy modeling research has been attempted to measure the literacy of Personal Finance with respect to their financial knowledge of different financial instrument and their practice or investment decisions. This study is based on stratified random sampling method with the help of financial literacy related parameters. This study has the intention to explore the skills of financial literacy; hence the objective was to test the basic financial knowledge of key products that is common to current society. In general, both categories have fairly healthy attitudes towards basic money management, financial planning and investment matters. Minorities of respondents of both categories save, monitor their spending and are generally responsible in the use of credit. Most of the respondents recognize the importance of financial planning and have done some basic financial planning. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 80-99 Uploaded date: July 8, 2012